ACTIVE AND PASSIVE OSMOTIC ADJUSTMENT IN OLIVE TREE LEAVES DURING DROUGHT STRESS - Boussadia, Olfa; Bchir, Amani; Steppe, Kathy; Van Labeke, Marie-Christine; Lemeur, Raoul; Braham, Mohamed (European Scientific Journal, ESJ, 2013)
We evaluated the osmotic adjustment capacity of two-year-old olive trees (Olea europaea L.) grown in pots in a greenhouse during a period of drought stress. Total osmotic adjustment increased with increasing severity of drought stress. Trees in the high stress treatment showed a total osmotic adjustment of 2.1 MPa and 2.8 MPa for the cultivars ‘Meski’ and ’Koroneiki’, respectively, 30 days after imposing drought stress. Osmotic adjustment allowed the leaves to reach total water potentials of -4.3 and -6.0 MPa for ‘Meski’ and ‘Koroneiki’, respectively. Osmotic adjustment (OA) in olive trees was associated with active (AOA) and passive (POA) osmotic regulation mechanisms. Using a regression analysis with some of the key osmoregulatory compounds (i.e. proline, soluble sugars and potassium), we found that ‘Koroneiki’ tends to adopt a passive strategy (POA) to tolerate progressive drought stress (confirmed by a reduction in leaf water content), while ‘Meski’ used an active strategy (AOA) and was able to maintain its leaf water content.